Continuous Criminal Accountability of Children as Perpetrators of Crimes of Decency - Angga Hardiansyah (Faculty of Law, Universitas Lampung, 2020)
Crimes committed by children today are increasingly diverse, one of which occurs in the jurisdiction of the Kalianda District Court, namely children as perpetrators of decency in the Decision on the Case of Number: 01/Pid.Sus-Anak/2015/PN.Kla. This research uses a normative and empirical juridical approach. The type of data used is primary data and secondary data. Primary data were obtained from interviews and secondary data sourced from literature study. The results showed that criminal liability against children as perpetrators of decency was continuously carried out with actions in the form of returning the Defendant to his parents to be nurtured and educated. The aim of criminal justice is to focus on the best interests of children integrated into the system and model of juvenile criminal justice, promoting integration into positive legal norms and the enforcement of child law. The purpose of punishment is not punishment, but improvement in conditions, care and protection of children. The basis for judges' legal considerations in imposing criminal sanctions is the prosecutor's indictment, the purpose of punishment, things that are lightening and burdensome, as well as applying several theories of legal objectives namely legal certainty, usefulness and legal justice. Suggestions in this study are that Judges should maximize the penalties imposed on each perpetrator of crimes against children, bearing in mind that crimes against children in Indonesia continue to increase so that this can be one of the judges' considerations in providing maximum crimes against perpetrators of moral offenses against children.